I Mannelli di Firenze - FOCARILE, PASQUALE (Premio Tesi di Dottorato, 2017)
The volume reconstructs the role of the "art objects" in the renewal of identity (social, political and cultural) of the Mannelli family, among the oldest families of the Florentine patriciate. During the 17th Century the main exponents adopted a lifestyle inspired by the Medici court, gradually dismantling, but at different times, the dress of the merchant. The analysis of the main town and countryside residences and of the displaying of the objects of art, conducted on a documentary basis and with the “display of art” critical tools, returns the fundamental stages of the renewal process and, together with numerous autonomous episodes of unpublished patronage and collecting, the emergence of common narrative strategies of historical and political identity through art objects.